Independent Review of the Crimes (Forensic Procedures) Act 2000 - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2003)
This Report focuses on the use of forensic procedures in the criminal justice system. It arises out of the requirement under section 122 of the Crimes (Forensic Procedures) Act 2000 (the Act) that the Minister (the Attorney General) review the Act to determine whether the policy objectives of the Act remain valid and whether the terms of the Act remain appropriate for securing those objectives.